Plasma exosomal miRNA expression and gut microbiota dysbiosis are associated with cognitive impairment in Alzheimer’s disease - Lin, Kaihao; Lin, Wenxia; Guo, Zhikai; Chen, Cuihong; Chen, Liang; Cai, Xianbin (Frontiers in Neuroscience, 2025)
IntroductionThe gut microbiota composition and the expression profiles of microRNAs (miRNAs) in the brain tissue, cerebrospinal fluid, and blood of patients with Alzheimer’s disease (AD) differ significantly from those with normal cognition function. The study aimed to initially explore the relationship between plasma exosomal microRNAs, gut microbiota, and cognitive impairment, providing insights into the pathogenesis and treatment of AD.MethodsThe study enrolled 8 participants with AD and 8 participants with normal cognition. The Mini-Mental State Examination (MMSE) was utilized to evaluate cognitive function. High-throughput sequencing was used to identify differentially expressed miRNAs in plasma exosomes, while metagenomic sequencing was employed to detect differences in the abundance of gut microbiota. Furthermore, the associations among them were analyzed.ResultsFour exosomal miRNAs and 14 microbiota taxa, which exhibited differential expression and abundance, respectively, in comparison between AD group and normal cognition group, were identified to be significantly associated with MMSE scores. Notably, the abundance of potential probiotics, including Faecalibacterium prausnitzii, Roseburia intestinalis and Roseburia inulinivorans, which was decreased in AD patients, exhibited positive correlations with specific exosomal miRNAs: Roseburia intestinalis correlated with miR-3120-3p and miR-6529-5p; Roseburia inulinivorans correlated with miR-3120-3p, miR-6529-5p and miR-124-3p; Faecalibacterium prausnitzii correlated with miR-3120-3p.DiscussionThe study revealed a close association among gut microbiota, plasma exosomal miRNAs, and cognitive impairment in AD, and suggested that specific components of gut microbiota and exosomal miRNAs may serve as potential biomarkers and therapeutic targets for AD on the microbiota-gut-brain axis.